2020
DOI: 10.3390/molecules25102369
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Effect of High Pressure Processing (HPP) on Gelatinization and Infusion of Nutrients

Abstract: High pressure processing (HPP) is a novel technology that involves subjecting foods to high hydrostatic pressures of the order of 100–600 MPa. This technology has been proven successful for inactivation of numerous microorganisms, spores and enzymes in foods, leading to increased shelf life. HPP is not limited to cold pasteurization, but has many other applications. The focus of this paper is to explore other applications of HPP, such as gelatinization, forced water absorption and infusion of nutrients. The us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…In this study, the quantification of RK4 in high-pressuretreated sample indicated that the component composition of foodstuffs is significantly modified by high-pressure treatment, and that such alterations may yield components other than RK4 with similar high bioactivities. High-pressure processing has been reported to be an innovative non-thermal food preservation method because it can inactivate microorganisms with minimal influence on the physicochemical and sensory properties of foods (40)(41)(42). However, there are few studies on the increase of the functional component(s) by high-pressure processing as far as we know.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the quantification of RK4 in high-pressuretreated sample indicated that the component composition of foodstuffs is significantly modified by high-pressure treatment, and that such alterations may yield components other than RK4 with similar high bioactivities. High-pressure processing has been reported to be an innovative non-thermal food preservation method because it can inactivate microorganisms with minimal influence on the physicochemical and sensory properties of foods (40)(41)(42). However, there are few studies on the increase of the functional component(s) by high-pressure processing as far as we know.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the monitored application of heat is the usual method of inducing a similar phenomenon and is routinely exploited in the manufacture and processing of brewing adjuncts. Several studies have shown that high-pressure leads to gelatinisation of cereal starches and boosts the efficiency of starch hydrolysis by αand β-amylases [107]. Therefore, it would be worth investigating whether high-pressure processing, which is an expensive technology, might be used in the research on the development of addition agents for enhanced processability of brewers' adjuncts in the beer industries.…”
Section: Future Trendsmentioning
confidence: 99%
“…This review mainly focuses on describing HPP sustainability, advantages, and limitations. HPP is an efficient, non-thermal, and the most accepted technique by the consumer [50]. Furthermore, the continuous demand for healthy and safe foods has discovered HPP for mild food preservation without chemicals and preservatives.…”
Section: Introductionmentioning
confidence: 99%